Colour difference evaluation for white light sources. (May 2015) - Luo, MR; Cui, G; Georgoula, M
An experiment was carried out to study colour discrimination on a display to simulate six different white light sources. Each centre includes 20 pairs of illuminant mode colours, which were assessed by 20 observers using the ratio method against a dark background. The results were used to test various models including the xy, uv, u ′ v ′ chromaticity diagrams; the CIELUV, CIELAB and CAM02-UCS uniform colour spaces and the CIEDE2000 colour-difference formula. The results showed that the models developed from illuminant mode colours such as u ′ v ′ and CIELUV predicted the results much more accurately than those developed from surface mode colours such as CIEDE2000 and CAM02-UCS. The present results lead us to propose the use of Δu ′ v ′ to set tolerances for all white light sources along the blackbody locus.